Missionary monks : an introduction to the history and theology of missionary monasticism - Smither, Edward L.; O'Loughlin, Thomas (Eugene, Oregon : Cascade Books, 2016)
Missionaries go into all the world and make disciples of all nations, while monks live cloistered in a monastery and focus their lives on prayer and studying Scripture--correct? Not exactly. When we study the history of Christian mission, especially from around 500 to 1500 CE, the key missionaries that we constantly encounter are monks. In fact, if we don't have monks in this period then we have very little in the way of Christian mission. Our aim in this book is to examine the phenomenon of missionary monks--those who pursued both a monastic and missionary calling. We will meet the monks and monastic orders, narrate their journeys in mission, and evaluate their approaches to and thoughts about mission.
Online resource; title from PDF title page (EBSCO, viewed February 23, 2017)
Includes bibliographical references and index.
Master record variable field(s) change: 072, 082
Keywords: Monasticism and religious orders -- History; Monastic and religious life -- History; Missions -- History; RELIGION / Christian Ministry / Missions; Electronic books